Political Branding Bupati Tuban Di Media Sosial Instagram - Surya, Andi; Harliantara; Nur’annafi Farni Syam Maella (Journal Communication Specialist, 2023)
AbstractAs a young politician who now serves as Regent of Tuban, political branding activities cannot stop here. Apart from being the number one person in Bumi Wali, this period was also the first period of his leadership. The importance of political branding for politicians is because branding provides identification value of the meaning, benefits and differentiation of a political product. Branding is able to influence consumer perceptions. Branding results from interactions between political contestants and constituents. By using a study of self-identification, political products and positioning from Mensah, Husnah and Suryawati. Researchers are trying to find out the political branding of the Regent of Tuban on Instagram social media. This researcher uses a qualitative type of research through content analysis. Qualitative research is research that aims to find out or understand what phenomena occur to a research subject. Meanwhile, content analysis focuses on the explicit content of communication messages. Not on the implied meaning of the message. The results of the analysis show that the Regent of Tuban tends to use the term "Mas Bupati" as an entity that refers to himself personally. Self-identification, shown by showing sympathy and empathy and achievement. Meanwhile, the "Mbangun Deso Noto Kuto" has become a mainstay political product. In the positioning aspect, this is done through updating existing programs. Apart from these three aspects, in political branding posts on Instagram, the Regent of Tuban uses many figures from national politicians and builds consensus with them as a characteristic.Keywords: Political Branding, Regent of Tuban, Instagram Abstrak Sebagai politisi muda yang kini menjabat sebagai Bupati Tuban, aktifitas political branding tidak boleh berhenti sampai di sini saja. Selain sebagai orang nomor satu di Bumi Wali, periode ini juga merupakan periode pertama dari kepemimpinannya. Pentingnya political branding untuk politisi disebabkan oleh, branding memberikan nilai identifikasi dari makna, manfaat, diferensiasi dari sebuah produk politik. Branding mampu mempengaruhi persepsi konstiuen. Branding hasil dari interaksi antara konstestan politik dan konstituen. Dengan mengunakan kajian identifikasi diri, produk politik dan positioning dari Mensah, Husnah dan Suryawati. Peneliti berusaha untuk mengetahui political branding Bupati Tuban di media Sosial Instagram. Dalam peneliti ini, mengunakan tipe penelitian kualitatif melalui analisis konten. Penelitian kualitatif adalah penelitian yang bertujuan untuk mengetahui atau memahami tentang fenomena-fenomena apa yang terjadi terhadap sebuah subjek penelitian. Sementara analisis konten berfokus pada isi pesan komunikasi yang tersurat. Bukan pada makna pesan yang tersirat. Hasil analisis menunjukan, Bupati Tuban cenderung mengunakan istilah “Mas Bupati” sebagai entitas yang merujuk pada dirinya secara pribadi. Identifikasi diri, ditunjukan dengan menampilkan rasa simpati dan empati dan berprestasi. Sementara jargon "Mbangun Deso Noto Kuto” menjadi produk politik andalan. Dalam aspek positioning, dilakukan melalui pembaharuan dari program-program yang telah ada. Di samping ketiga aspek tersebut, dalam postingan political branding di Instagram, Bupati Tuban banyak mengunnakan ketokohan dari politisi nasional dan membangun konsesus dengan mereka sebagai ciri khas.Kata Kunci : Political Branding, Bupati Tuban, Instagram